2015
DOI: 10.1111/age.12391
|View full text |Cite
|
Sign up to set email alerts
|

Tropically adapted cattle of Africa: perspectives on potential role of copy number variations

Abstract: Africa is host to diverse and locally adapted cattle breeds that are expected to survive the harsh and extreme tropical environments associated with diseases and parasite infections, heat stress and episodes of feed and water scarcity. Genomic copy number variations (CNVs) are considered to be primary role players in cattle breed formation and adaptation where isolation and genetic drift together with subsequent mutations have created an enormous diversity of local populations. CNVs are modifications in DNA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 96 publications
(167 reference statements)
0
10
0
Order By: Relevance
“…; Wang et al . ; Pitt et al . ), we found a number of differentially methylated genes between Creole and Spanish groups implicated in several biological processes, such as immunity, nervous system processes, energy management, heat resistance and skin and coat attributes, which are key for survival in harsh environments (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Wang et al . ; Pitt et al . ), we found a number of differentially methylated genes between Creole and Spanish groups implicated in several biological processes, such as immunity, nervous system processes, energy management, heat resistance and skin and coat attributes, which are key for survival in harsh environments (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…; Wang et al . ; Pitt et al . ), we lack understanding of relevant epigenetic function (see Varriale for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Gifford‐Gonzalez & Hanotte, ; Linseele, ). In addition, breed diversification has been a major factor in the zoogeography of African livestock, enabling domesticates to live in a wide variety of modern ecological zones (Bahbahani et al, ; Murray & Trail, ; Mwai, Hanotte, Kwon, & Cho, ; Wang, Dzama, Rees, & Muchadeyi, ). Thus, the broadening of the animal production climatic niche is associated with evolutionary trends, and it is highly likely that these were the mechanism for expansion of the climatic land use niche for domestic animals that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal a close connection between genomic regions associated with morphometric traits and adaptive traits. For instance, two of the identified variants detected for morphometric traits in this study are directly linked to immune response, while several potential candidate genes have functional annotations for, e.g., signal transduction, metabolism, and immune response adaptation [134]. The comparison with previous studies confirms associations of the identified genes with selection signatures as well as immunity or resistance to diseases, feed efficiency and adaptation to harsh environments (heat stress, high altitude), addressing the main components of adaptation [4].…”
Section: Genomic Regions Associated With Morphometric and Adaptation mentioning
confidence: 96%